Consequences of air pollution among traffic police in selected areas of metropolitan cities of Kathmandu valley. - Kafle,Poonam (2017)
ABSTRACT: Air pollution in Kathmandu bas become a major issue in today's context traffic police are at the high risk as they constantly have to be exposed in the environment . The general objective of the study was to assess the consequences of air pollution among traffic police in selected areas of Kathmandu district. The study design was cross-sectional descriptive study. Highly traffic burden areas and major intersection roads of Kathmandu Valley were selected for the study. The selected areas were Satdobato, Kalanki ,Singhdurbar, Koteshwor, Thankot , Kalimati, Maharajgunj and thapathali. The study variables were health status of traffic police, age sex , knowledge , duration exposure, PPE, smoking , alcoholism and periodic check us. The required sample size was 174. For the selection of study areas, purposive sampling was used. For the selection of traffic police, convenient sampling was used. Semi-structured questionnaire was used as tool of data collection and face-to-face interview of each traffic policemen was taken for the study. After the data was collected, it was checked on a daily basis for it completeness . Collected data was coded and was entered and analysed in Statistical for Social Sciences(SPSS). Interpretation was done in the form of table. All the traffic police (both male and female) who were available at the time of data collection included. The study found that about 80% of the respondents suffered from respiratory problems like cough, chest pain and difficulty in breathing. The majority of traffic police (94.9%) used masks. Majority of the respondents were of age group 20-30. More than 80% of the respondents were male(88.8%). Most of the respondents had completed their +2 level(70.1%). All the respondents (100%) knew about the air pollution. The major cause of increasing air pollution in Kathmandu valley was found to be road expansion (94.4%). Another cause air pollution was use of old vehicles(78.5%). air pollution has badly affected the health of traffic police. The major health problems seen due to air pollution was respiratory problem(81.3%0 followed by eye problems (69.3%). More than 80% of the respondents complained about regular common cold and cough (83.4%0. Other respiratory problems were chest pain (44.6%) and difficulty in breathing(38.3%0. All the respondents (100%) were aware about the PPE and mostly used PPE was mask(94.9%). 16.4% of the respondents had the habit of smoking regularly and 16.4% of the respondents had the habit of consuming alcohol.